Ultraviolet window electrode and preparation method and application thereof
By preparing acetylcelasuronette -based protective layer on the surface of the silver nano -wiring thin film, the existing UV -window electrode material binding force is low and easy to be oxidized, and ultraviolet detectors with high response, stable signals and long life.
Patent Information
- Application Number
- CN202411412650.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-11
AI Technical Summary
Existing ultraviolet window electrode materials, such as silver nanowires, have problems such as low binding force, poor interface bonding, large contact resistance and easy oxidation, resulting in low detector responsiveness and poor stability.
Hafnium acetylacetonate is used as the hafnium source, dissolved in a mixed solvent composed of methanol, ethylene glycol methyl ether and glacial acetic acid to form a protective layer precursor, which is spin-coated on the surface of the silver nanowire film and annealed to form a composite protective layer to enhance the electrode adhesion and antioxidant properties.
Improve the transparency, conductivity and antioxidant performance of the electrode of the ultraviolet window, enhance the response and signal stability of the detector, and extend the service life.
Smart Images

Figure CN119364918A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrode film preparation, and in particular to an ultraviolet window electrode and a preparation method and application thereof. Background Art
[0002] Ultraviolet photoelectric detection technology is a technology that uses the response characteristics of semiconductor materials or other specific materials to ultraviolet light for detection. The application range of ultraviolet light is extremely wide, covering many important fields such as environmental monitoring, communication technology, military reconnaissance and biomedicine. Ultraviolet detectors are crucial to these applications. Among them, heterojunction ultraviolet detectors are the key technology for achieving efficient ultraviolet light detection due to their excellent response speed, low dark current and stable performance.
[0003] Heterojunction UV detectors have high requirements for window electrodes. However, the existing electrode materials, such as indium tin oxide (ITO), fluorine-doped tin oxide (FTO), and aluminum-doped zinc oxide (AZO), have insufficient bandgap and low transmittance to short-wave ultraviolet rays. Therefore, when used as window electrodes, their detection wavelength is generally limited to the long-wave ultraviolet region (320~400nm). Although some literature reports on photoconductive structures and heterojunction structure detectors that do not require window electrodes, the detection limit can reach deep ultraviolet. In the prior art, interdigitated electrodes are used as windows. However, due to the poor conductivity of ultraviolet detection materials, the small electrode spacing, and the low light utilization rate, the device response is low and is not suitable for promotion and use. There are also some reports in the prior art that use silver nanowires, graphene and other nano-ultraviolet transparent conductive materials as electrodes and ultraviolet detectors. However, these electrode materials also have many problems. For example, silver nanowires have excellent conductivity, flexibility and light transmittance, and the process of preparing them into conductive films is simple. They are widely selected window electrode materials in this field. However, the films prepared from silver nanowires have low bonding strength with the detection materials and loose interface bonding. The signal stability is poor and difficult to guarantee under conditions of large working current. Secondly, the silver nanowires themselves have the problem of large contact resistance. Excessive contact resistance will reduce the photoelectric performance and device stability of the silver nanowire film. Finally, silver nanowires are easily oxidized as electrode materials. In order to solve the problems of poor bonding strength and easy oxidation of silver nanowire films, a protective layer is usually prepared on their surface, but this will reduce the light transmittance of the silver nanowire film. Summary of the invention
[0004] Based on the above technical problems, the present invention aims to provide an ultraviolet window electrode.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned ultraviolet window electrode. The ultraviolet window electrode prepared by this method has high transparency, good conductivity, strong adhesion on the surface of ultraviolet detection materials, excellent antioxidant performance, high detector responsiveness, stable detection signal, and long service life.
[0006] The third object of the present invention is to provide applications of the above-mentioned ultraviolet window electrode.
[0007] The purpose of the present invention is achieved through the following technical solutions: A UV window electrode, characterized in that: the electrode is a composite thin film electrode formed by a silver nanowire film and a protective layer prepared from hafnium acetylacetonate, the composite thin film electrode comprising a silver nanowire film and a protective layer on its surface, the protective layer being a protective layer precursor liquid formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent consisting of methanol, ethylene glycol methyl ether and glacial acetic acid, spin-coated on the surface of the silver nanowire film, and then annealed to form a film layer composed of a composite component.
[0008] Furthermore, the concentration of hafnium acetylacetonate in the protective layer precursor solution is 0.1-2.0 mol / L, the volume ratio of methanol to ethylene glycol methyl ether in the mixed solvent is 1:6-4:1, and the amount of glacial acetic acid added is 2-10% of the total volume of the solution.
[0009] Furthermore, the annealing temperature is 90-140° C., and the annealing time is 12-48 h.
[0010] More preferably, the annealing is first annealing at 90-100° C. for 0.5-2 h, and then annealing at 120-160° C. for 12-48 h.
[0011] A method for preparing an ultraviolet window electrode is characterized in that: a silver nanowire film is prepared on the surface of an ultraviolet detection material film, and then a protective layer is prepared on the surface of the silver nanowire film to form a composite ultraviolet window electrode, wherein the protective layer is a film layer composed of composite components formed by spin coating a protective layer precursor solution formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent, and then annealing, wherein the mixed solvent is composed of methanol, ethylene glycol methyl ether and glacial acetic acid, wherein hafnium acetylacetonate has a large solubility in methanol, so methanol is the main solvent for dissolving hafnium acetylacetonate; ethylene glycol methyl ether is used as an auxiliary solvent to prevent the single methanol solvent from volatilizing quickly, and can also improve the wettability of the solution to certain films (such as nickel oxide films); glacial acetic acid is used as a stabilizer to prevent hafnium acetylacetonate from contacting water vapor in the air and precipitating, and can be easily removed during heating.
[0012] Furthermore, the concentration of hafnium acetylacetonate in the protective layer precursor solution is 0.1-2.0 mol / L, the volume ratio of methanol to ethylene glycol methyl ether in the mixed solvent is 1:6-4:1, and the amount of glacial acetic acid added is 2-10% of the total volume of the solution.
[0013] Furthermore, the annealing temperature is 90-140° C., and the annealing time is 12-48 h.
[0014] More preferably, the annealing is first annealing at 90-100° C. for 0.5-2 h, and then annealing at 120-160° C. for 12-48 h.
[0015] The purpose of annealing at a lower temperature of 90-100 °C is to volatilize, initially pyrolyze and solidify the hafnium acetylacetonate solution, while ensuring that the electrical properties of the silver nanowires will not degrade due to excessive annealing temperatures. After the above steps, the silver nanowires have achieved initial protection, and their high temperature and oxidation resistance have been improved. Then, annealing at a higher temperature of 120-160 °C is performed to fully pyrolyze the hafnium acetylacetonate, further improving the stability and optical transmittance of the window electrode.
[0016] When silver nanowires are used to prepare window electrodes, in order to ensure the light transmittance of the silver nanowire film while solving the problems in the prior art that the film prepared by the silver nanowires has low bonding force with the detection material and the interface bonding is not tight, and secondly, the silver nanowires themselves also have too high contact resistance, which will reduce the photoelectric performance and device stability of the silver nanowire film, and the silver nanowires are easily oxidized as electrode materials. In the present invention, hafnium acetylacetonate is dissolved in a composite organic solvent to prepare a precursor solution. After the silver nanowire film is deposited, the precursor solution is deposited on its surface, and then annealed to prepare a protective layer. Due to the annealing step and the choice of solvent, the components and grain structure of the final pyrolyzed hafnium acetylacetonate are significantly affected, and the properties of the protective layers with different components and different grain structures will also be different. In the annealing process, the present invention controls the annealing temperature and time, and combines the different components in the solvent to volatilize to different degrees in a specific annealing step, so that the hafnium acetylacetonate forms a complex decomposition and crystallization process during the annealing process, and generates a protective layer with a composition between hafnium acetylacetonate and hafnium oxide. The protective layer film is attached to the silver nanowire film, forming a dense structure with uniform distribution of various components, forming a good coating for the silver nanowires, and reflecting excellent interface bonding. In addition, the composite electrode formed by the composite of the protective layer and the silver nanowire film effectively improves the charge transfer performance of the electrode.
[0017] Most specifically, a method for preparing an ultraviolet electrode window electrode is characterized by comprising the following steps: Silver nanowire ink with a solid content of 10 g / L and a diameter of 30-80 nm was deposited on the substrate surface to form a silver nanowire film with a thickness of 20-60 nm. A protective layer precursor liquid is deposited on the surface of a silver nanowire film, and then annealing is performed to form a protective layer composed of a composite component. The annealing temperature is 90-160°C, the annealing time is 12-48 h, and the thickness of the prepared protective layer is 40-100 nm. The protective layer precursor liquid uses hafnium acetylacetonate as a hafnium source and is dissolved in a mixed solvent to form a protective layer precursor liquid with a concentration of 0.1-2.0 mol / L. The mixed solution is composed of methanol, ethylene glycol methyl ether and glacial acetic acid, wherein the volume ratio of methanol to ethylene glycol methyl ether is 1:6-4:1, and the amount of glacial acetic acid added is 2-10% of the total volume of the solution.
[0018] The application of the above-mentioned ultraviolet window electrode in ultraviolet detection is specifically applied to the preparation of ultraviolet detectors.
[0019] The detector adopts a vertical heterojunction structure, the first layer of the structure is a conductive substrate, including but not limited to molybdenum glass, ITO glass or FTO glass, preferably ITO glass, and the second layer is an n-type semiconductor film, including but not limited to ZnO, TiO 2 Thin film, preferably TiO 2 Thin film, the third layer is Bi 2 O 3 The middle layer is used to improve the signal stability and responsiveness of the detector. The fourth layer is a p-type semiconductor film, including but not limited to MoO 3 , WO 3 and NiO film, preferably NiO film, the fifth layer of the protective layer and the composite ultraviolet window electrode formed by silver nanowires.
[0020] A method for preparing an ultraviolet detector, characterized in that it comprises the following steps: Preparation of semiconductor conductive devices Positive structure: ITO glass is used as the substrate, and TiO is prepared by spin coating on its surface. 2 Thin films, in TiO 2 The film surface was spin-coated to prepare Bi 2 O 3 The middle layer and the NiO film form a positive structure conductive device; Preparation of composite electrodes A silver nanowire film with a solid content of 10 g / L and a diameter of 30-80 nm is prepared on the surface of a conductive device, and the film thickness is 20-60 nm. A protective layer is then prepared on the surface of the silver nanowire film to form a composite ultraviolet window electrode. The protective layer is formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent, and the protective layer precursor is spin-coated on the surface of the silver nanowire film. The protective layer is first annealed at 90-100 ° C for 0.5-2 h, and then annealed at 120-160 ° C for 12-48 h. The prepared protective layer has a thickness of 40-100 nm. The protective layer precursor is formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent to form a protective layer precursor with a concentration of 0.1-2.0 mol / L. The mixed solution is composed of methanol, ethylene glycol methyl ether and glacial acetic acid, wherein the volume ratio of methanol to ethylene glycol methyl ether is 1:6-4:1, and the amount of glacial acetic acid added is 2-10% of the total volume of the solution. Silver glue is used to make electrode pins in the electrode film and the ITO blank area to obtain a complete ultraviolet photodetector.
[0021] In order to facilitate testing or better lead-out electrodes, the window electrode can be patterned. For example, with the help of a mask, the silver nanowire film is first patterned, and then a protective layer film is prepared. Alternatively, a complete silver nanowire film can be prepared, and a protective layer film is prepared on its surface using a mask, and then the silver nanowires outside the mask pattern are removed.
[0022] The present invention has the following technical effects: In the present invention, a precursor solution is prepared with hafnium acetylacetonate, and a dense protective layer composed of complex components is prepared on the surface of the silver nanowire film, thereby forming a composite window electrode, which completely wraps the silver nanowire film, ensures that the electrode has high light transmittance, effectively improves the interface bonding force between the electrode and the conductive device, improves the charge collection efficiency and transmission stability, thereby improving the detection performance of the detector, and at the same time enables the ultraviolet detection device to have good environmental stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : Schematic diagram of the detector structure of the composite ultraviolet window electrode composed of a silver nanowire film and a protective layer film prepared by the present invention.
[0024] Figure 2 : A scanning electron microscope photograph of the composite ultraviolet window electrode prepared in Example 1 of the present invention.
[0025] Figure 3 : Transmittance curves of the composite UV window electrode and the unprotected silver nanowire film electrode prepared in Example 1 of the present invention.
[0026] Figure 4 : Photograph of the detector prepared in Example 1 of the present invention.
[0027] Figure 5 : Test results of the composite ultraviolet window electrode tape prepared in Example 1 of the present invention.
[0028] Figure 6 : Comparison of the IT response characteristic curves of the detector prepared in Example 1 of the present invention to ultraviolet light of different bands.
[0029] Figure 7 : Comparison of the photocurrent variation over time between the detector of the present invention and the detector with UV window electrode without protected silver nanowires.
[0030] Figure 8 : Noise density comparison between the detector of the present invention and the detector with UV window electrode without protected silver nanowires. DETAILED DESCRIPTION
[0031] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.
[0032] A method for preparing an ultraviolet detector comprises the following steps: Preparation of semiconductor conductive devices Prepare precursor solution: dissolve isopropyl titanate in ethanol to prepare a TiO 2 Precursor solution: dissolve bismuth nitrate in ethylene glycol methyl ether to prepare a Bi solution with a concentration of 0.1~0.2 mol / L. 2 O 3 Precursor solution: dissolving nickel acetylacetonate or nickel acetate in ethylene glycol methyl ether to prepare a NiO precursor solution with a concentration of 0.1-2.0 mol / L; Preparation of positive structure: ITO glass is used as the substrate, one side of which is covered with a small area of polyimide high temperature resistant tape, and TiO is spin coated on the ITO glass. 2 Precursor solution, then annealed at 450-500℃ for 20-45min to obtain a 10-50nm thick TiO 2 film; then continue on TiO 2 Bi is spin-coated on the film surface 2 O 3 Precursor solution, after spin coating, anneal at 400~500℃ for 20~45 min to prepare Bi with a thickness of 10~20 nm 2 O 3 Thin film; then in Bi 2 O 3The NiO precursor solution is spin-coated on the film surface, and annealed at 350-450°C for 10-30 minutes to obtain a 10-30 nm thick NiO film; a positive structure conductive device is formed; Preparation of composite electrodes A silver nanowire film with a solid content of 10 g / L and a diameter of 30-80 nm is prepared on the surface of a conductive device, and the film thickness is 20-60 nm. A protective layer is then prepared on the surface of the silver nanowire film to form a composite ultraviolet window electrode. The protective layer is formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent. The protective layer precursor is spin-coated on the surface of the silver nanowire film, first annealed at 90-100 ° C for 0.5-2 h, and then annealed at 120-160 ° C for 12-48 h. The prepared protective layer has a thickness of 40-100 nm. The protective layer precursor is formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent to form a protective layer precursor with a concentration of 0.1-2.0 mol / L. The mixed solution is composed of methanol, ethylene glycol methyl ether and glacial acetic acid, wherein the volume ratio of methanol to ethylene glycol methyl ether is 1:6-4:1, and the amount of glacial acetic acid added is 2-10% of the total volume of the solution. Silver glue is used to make electrode pins in the electrode film and the ITO blank area to obtain a complete ultraviolet photodetector.
[0033] Example 1 A method for preparing an ultraviolet detector comprises the following steps: Preparation of semiconductor conductive devices Prepare precursor solution: dissolve isopropyl titanate in ethanol to prepare a TiO 2 Precursor solution: dissolving nickel acetylacetonate or nickel acetate in ethylene glycol methyl ether to prepare a NiO precursor solution with a concentration of 0.25 mol / L; Preparation of positive structure: ITO glass is used as the substrate, one side of which is covered with a small area of polyimide high temperature resistant tape, and TiO is spin coated on the ITO glass. 2 The TiO with a thickness of 30 nm was prepared by annealing at 460 °C for 30 min. 2 film; then continue on TiO 2 Spin coating Bi on the film surface 2 O 3 Precursor solution, annealed at 450℃ for 30 min after spin coating, to prepare Bi with a thickness of about 15 nm 2 O 3 Thin film; then in Bi 2 O 3 The NiO precursor solution was spin-coated on the film surface and annealed at 400 °C for 20 min to prepare a NiO film with a thickness of 20 nm; a positive structure conductive device was formed; Preparation of composite electrodes A silver nanowire film with a solid content of 10 g / L and a diameter of 30-80 nm is prepared on the surface of a conductive device. The film thickness is 40 nm and the square resistance is 10 Ω / sq. A protective layer is then prepared on the surface of the silver nanowire film to form a composite ultraviolet window electrode. The protective layer is formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent. The protective layer precursor is spin-coated on the surface of the silver nanowire film. The protective layer is first annealed at 100°C for 0.5 h and then annealed at 140°C for 14 h. The prepared protective layer has a thickness of 50 nm. The protective layer precursor is formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent to form a protective layer precursor with a concentration of 2.0 mol / L. The mixed solution is composed of methanol, ethylene glycol methyl ether and glacial acetic acid, wherein the volume ratio of methanol to ethylene glycol methyl ether is 1:1, and the amount of glacial acetic acid added is 5% of the total volume of the solution. Finally, the polyimide high temperature resistant tape was peeled off, and silver glue was used to make electrode pins on the electrode film and the ITO blank area to obtain a complete ultraviolet photodetector.
[0034] Figure 1 This is a schematic diagram of the detector structure based on the composite ultraviolet window electrode prepared in the present invention. Figure 2 This is a scanning electron microscope photo of the composite UV window electrode prepared in Example 1 of the present invention, where a is an unprotected silver nanowire thin film electrode, and b is a UV window electrode with a pyrolyzed hafnium acetylacetonate protective layer deposited on the surface. It can be seen from the figure that the AgNWs are covered in the pyrolyzed hafnium acetylacetonate protective layer, the surface is dense, and there are few cracks and holes.
[0035] Figure 3 The transmittance curves of the composite UV window electrode (blue) and the unprotected silver nanowire film electrode (red) prepared in Example 1 of the present invention are shown. As can be seen from the figure, the composite UV window electrode has good transmittance in the entire UV region, and the transmittances at 254 nm and 310 nm are 65.8% and 63.7% respectively, which are slightly lower than the 70.9% and 77.8% of the pure silver nanowire film, indicating that the coverage of the protective layer has little effect on the UV transmittance of the electrode.
[0036] Figure 4 This is a photo of the detector prepared in Example 1 of the present invention. Figure 5 The results of the tape test of the prepared detector containing the composite UV window electrode. According to the steps in the figure, the electrode in the detector did not fall off, and the square resistance did not change significantly, indicating that the composite UV window electrode UV film has good adhesion strength and can improve the device's usability.
[0037] According to the method of Example 1, a detector was prepared with a single silver nanowire thin film window electrode as a control group, and compared with the detector prepared in Example 1. Figure 6 The it response characteristic curves of the detectors prepared in Example 1 of the present invention and the control group to ultraviolet light of different bands are compared. Compared with the simple silver nanowire electrode, the detection performance of the composite ultraviolet window electrode is improved to a certain extent. For example, at a power density of 5 μWcm -2 Under 254 nm ultraviolet light, the photocurrent of the detector with the composite ultraviolet window as the electrode is 0.82 μA, which is higher than the 0.67 μA of the detector with a simple silver nanowire electrode. The reason is that the pyrolysis of hafnium acetylacetonate increases the binding of the silver nanowires in the composite ultraviolet window electrode to the detector film surface, reducing the contact resistance between the silver nanowires. In comparison, the simple silver nanowires adhere to the detector film surface by physical contact, with weak adhesion and poor contact tightness, resulting in reduced charge transfer and collection efficiency.
[0038] Figure 7 The photocurrent of the detector of the present invention is compared with that of the detector with UV window electrode without protection of silver nanowires. It can be seen from the figure that the performance of the detector with composite UV window electrode protected by pyrolyzed hafnium acetylacetonate remains stable after being placed in the environment for 90 days. -2 Under 254 nm ultraviolet light, the photocurrent remains almost constant at 0.82-0.83 μA. However, the detector using a pure silver nanowire UV window electrode showed obvious attenuation due to the gradual oxidation of the silver nanowires in the environment. Under the same conditions, the photocurrent dropped rapidly from 0.67 μA to 0.39 μA within one month, and further dropped to 0.27 μA after three months. Pyrolysis of hafnium acetylacetonate can also reduce the current noise of silver nanowires. Figure 8 As can be seen from the figure, the detector is protected by silver nanowires protected by pyrolyzed hafnium acetylacetonate as the window electrode. -3 The current noise density in the frequency range of 10 Hz-50 Hz is significantly reduced, which indicates that the detector has a better gain effect when amplifying the signal.
[0039] Example 2 A method for preparing an ultraviolet detector comprises the following steps: Preparation of semiconductor conductive devices Prepare precursor solution: dissolve isopropyl titanate in ethanol to prepare a TiO 2 Precursor solution: dissolving nickel acetylacetonate or nickel acetate in ethylene glycol methyl ether to prepare a NiO precursor solution with a concentration of 0.25 mol / L; Preparation of positive structure: ITO glass is used as the substrate, one side of which is covered with a small area of polyimide high temperature resistant tape, and TiO is spin coated on the ITO glass. 2 The TiO with a thickness of 30 nm was prepared by annealing at 460 °C for 30 min. 2 film; then continue on TiO 2 Bi is spin-coated on the film surface 2 O 3 Precursor solution, annealed at 450℃ for 30 min after spin coating, to prepare Bi with a thickness of about 15 nm 2 O 3 Thin film; then in Bi 2 O 3 The NiO precursor solution was spin-coated on the film surface and annealed at 400 °C for 20 min to prepare a NiO film with a thickness of 20 nm; a positive structure conductive device was formed; Preparation of composite electrodes A silver nanowire film with a solid content of 10 g / L and a diameter of 30-80 nm is prepared on the surface of a conductive device. The film thickness is 40 nm and the square resistance is 10 Ω / sq. A protective layer is then prepared on the surface of the silver nanowire film to form a composite ultraviolet window electrode. The protective layer is a protective layer precursor liquid formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent and spin-coated on the surface of the silver nanowire film. The protective layer is first annealed at 90°C for 2 h and then annealed at 160°C for 12 h to form a film layer composed of a composite component. The prepared protective layer has a thickness of 50 nm. The protective layer precursor liquid is a protective layer precursor liquid with a concentration of 1.5 mol / L formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent. The mixed solution is composed of methanol, ethylene glycol methyl ether and glacial acetic acid, wherein the volume ratio of methanol to ethylene glycol methyl ether is 1:6, and the amount of glacial acetic acid added is 2% of the total volume of the solution. Finally, the polyimide high temperature resistant tape was peeled off, and silver glue was used to make electrode pins on the electrode film and the ITO blank area to obtain a complete ultraviolet photodetector.
[0040] Comparative Example 1 Compared with Example 2, when preparing the protective layer precursor solution, an equal volume of methanol is used to replace ethylene glycol methyl ether to form a composite solvent with glacial acetic acid, and the remaining steps are the same as in Example 2.
[0041] Comparative Example 2 Compared with Example 2, during annealing, the annealing treatment was carried out at a constant temperature of 160° C. for 16 h, and the remaining steps were the same as those in Example 2.
[0042] By comparing the performance of the UV detectors prepared in Example 2, Comparative Example 1 and Comparative Example 2, the photocurrent test was performed at a power density of 5 μWcm -2The test was conducted under 254 nm ultraviolet light, and the detector without protective layer was used as a control. Specifically, when preparing the electrode, no protective layer was deposited, but the same annealing treatment as in Example 2 was performed. The results are shown in Table 1.
[0043] Table 1:
[0044] As can be seen from the table, in the control group without any protective layer, although the ultraviolet light transmittance is high, the initial photocurrent is significantly lower, and after 90 days, the photocurrent drops to 0.25 μA due to the serious failure of the silver nanowire film layer without long-term protection. Although the initial ultraviolet light transmittance is slightly lower in Example 2 of the present invention, the initial photocurrent is significantly improved, and the photocurrent stability after 90 days has not changed, which shows that under the action of the protective layer, the silver nanowires are stable and have not failed. Compared with Example 2, the ultraviolet light transmittance of Comparative Examples 1 and 2 further decreases, and the initial photocurrent is also significantly lower. This is because under different solvents, that is, annealing conditions, the thermal decomposition and crystallization process of hafnium acetylacetonate in the protective layer change, and the components in the protective layer have different primary grain structures, which makes the performance of the protective layer formed in the end significantly different, and the direct high temperature annealing in Comparative Example 2 causes the silver nanowires to form no initial protection during the initial annealing. The silver nanowires are damaged to a certain extent during the annealing process, and the initial current density has dropped significantly.
[0045] Example 3 A method for preparing an ultraviolet detector comprises the following steps: Preparation of semiconductor conductive devices Prepare precursor solution: dissolve isopropyl titanate in ethanol to prepare a TiO 2 Precursor solution: dissolving nickel acetylacetonate or nickel acetate in ethylene glycol methyl ether to prepare a NiO precursor solution with a concentration of 0.1 mol / L; Preparation of positive structure: ITO glass is used as the substrate, one side of which is covered with a small area of polyimide high temperature resistant tape, and TiO is spin coated on the ITO glass. 2 Precursor solution, then annealed at 450℃ for 45min to prepare 50nm thick TiO 2 film; then continue on TiO 2 Bi is spin-coated on the film surface 2 O 3 Precursor solution, annealed at 450℃ for 30 min after spin coating, to prepare Bi with a thickness of about 10 nm 2 O 3 Thin film; then in Bi 2 O 3The NiO precursor solution was spin-coated on the film surface and annealed at 350°C for 30 min to obtain a 30 nm thick NiO film; a positive structure conductive device was formed; Preparation of composite electrodes A silver nanowire film with a solid content of 10 g / L and a diameter of 30-80 nm is prepared on the surface of a conductive device. The film thickness is 60 nm and the square resistance is 10 Ω / sq. A protective layer is then prepared on the surface of the silver nanowire film to form a composite ultraviolet window electrode. The protective layer is a protective layer precursor solution formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent and spin-coated on the surface of the silver nanowire film. The protective layer is annealed at 140°C for 14 h. The prepared protective layer has a thickness of 100 nm. The protective layer precursor solution is a protective layer precursor solution with a concentration of 1.0 mol / L formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent. The mixed solution is composed of methanol, ethylene glycol methyl ether and glacial acetic acid, wherein the volume ratio of methanol to ethylene glycol methyl ether is 4:1, and the amount of glacial acetic acid added is 10% of the total volume of the solution. Finally, the polyimide high temperature resistant tape was peeled off, and silver glue was used to make electrode pins on the electrode film and the ITO blank area to obtain a complete ultraviolet photodetector.
[0046] The UV detector prepared in this example has a power of 5 μWcm -2 The photocurrent remained almost constant at 0.68-0.71 μA under 254 nm ultraviolet illumination for 90 days.
[0047] Example 4 A method for preparing an ultraviolet detector comprises the following steps: Preparation of semiconductor conductive devices Prepare precursor solution: dissolve isopropyl titanate in ethanol to prepare a TiO 2 Precursor solution: dissolving nickel acetylacetonate or nickel acetate in ethylene glycol methyl ether to prepare a NiO precursor solution with a concentration of 1.0 mol / L; Preparation of positive structure: ITO glass is used as the substrate, one side of which is covered with a small area of polyimide high temperature resistant tape, and TiO is spin coated on the ITO glass. 2 Precursor solution, and then annealed at 500 °C for 20 min to obtain a 10 nm thick TiO 2 film; then continue on TiO 2 Spin coating Bi on the film surface 2 O 3 Precursor solution, annealed at 450℃ for 30 min after spin coating, to prepare Bi with a thickness of about 20nm 2 O 3 Thin film; then in Bi 2 O 3 The film surface is then2 The film was spin-coated with NiO precursor solution and annealed at 450 °C for 10 min to obtain a 10 nm thick NiO film; a positive structure conductive device was formed; Preparation of composite electrodes A silver nanowire film with a solid content of 10 g / L and a diameter of 30-80 nm is prepared on the surface of a conductive device. The film thickness is 20 nm and the square resistance is 10 Ω / sq. A protective layer is then prepared on the surface of the silver nanowire film to form a composite ultraviolet window electrode. The protective layer is a protective layer precursor liquid formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent and spin-coated on the surface of the silver nanowire film. The protective layer is first annealed at 100°C for 1 h and then annealed at 120°C for 48 h to form a film layer composed of a composite component. The prepared protective layer has a thickness of 40 nm. The protective layer precursor liquid is a protective layer precursor liquid with a concentration of 0.1 mol / L formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent. The mixed solution is composed of methanol, ethylene glycol methyl ether and glacial acetic acid, wherein the volume ratio of methanol to ethylene glycol methyl ether is 2:1, and the amount of glacial acetic acid added is 5% of the total volume of the solution. Finally, the polyimide high temperature resistant tape was peeled off, and silver glue was used to make electrode pins on the electrode film and the ITO blank area to obtain a complete ultraviolet photodetector.
[0048] The UV detector prepared in this example has a power of 5 μWcm -2 The photocurrent remained almost constant at 0.74-0.75 μA under 254 nm UV illumination for 90 days.
Claims
1. An ultraviolet window electrode, characterized in that: The electrode is a composite thin film electrode formed by a silver nanowire film and a protective layer prepared from hafnium acetylacetonate. The composite thin film electrode includes a silver nanowire film and a protective layer on its surface. The protective layer is a protective layer precursor liquid formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent consisting of methanol, ethylene glycol methyl ether and glacial acetic acid, which is spin-coated on the surface of the silver nanowire film and then annealed to form a film layer composed of composite components.
2. An ultraviolet window electrode as claimed in claim 1, characterized in that: The concentration of hafnium acetylacetonate in the protective layer precursor solution is 0.1-2.0 mol / L, the volume ratio of methanol to ethylene glycol methyl ether in the mixed solvent is 1:6-4:1, and the amount of glacial acetic acid added is 2-10% of the total volume of the solution.
3. An ultraviolet window electrode as claimed in claim 1 or 2, characterized in that: The annealing is first annealing at 90-100°C for 0.5-2 h, and then annealing at 120-160°C for 12-48 h.
4. A method for preparing an ultraviolet window electrode, characterized in that: A silver nanowire film is prepared on the surface of an ultraviolet detection material film, and then a protective layer is prepared on the surface of the silver nanowire film to form a composite ultraviolet window electrode. The protective layer is a protective layer precursor liquid formed by dissolving hafnium acetylacetonate as a hafnium source in a mixed solvent, which is spin-coated on the surface of the silver nanowire film and then annealed to form a film layer composed of composite components. The mixed solvent is composed of methanol, ethylene glycol methyl ether and glacial acetic acid.
5. The method for preparing an ultraviolet window electrode according to claim 4, characterized in that: The concentration of hafnium acetylacetonate in the protective layer precursor solution is 0.1-2.0 mol / L, the volume ratio of methanol to ethylene glycol methyl ether in the mixed solvent is 1:6-4:1, and the amount of glacial acetic acid added is 2-10% of the total volume of the solution.
6. A method for preparing an ultraviolet window electrode as claimed in claim 4 or 5, characterized in that: The annealing temperature is 90-140° C., and the annealing time is 12-48 h. Preferably, the annealing is performed at 90-100° C. for 0.5-2 h, and then at 120-160° C. for 12-48 h.
7. The method for preparing an ultraviolet window electrode according to claim 6, characterized in that: The silver nanowire film is formed by depositing silver nanowire ink with a solid content of 10 g / L and a diameter of 30-80 nm onto the surface of a substrate.
8. Application of the ultraviolet window electrode prepared by the method of claim 7 in ultraviolet detection, specifically in the preparation of ultraviolet detectors.
9. The use of the ultraviolet window electrode as claimed in claim 8 in ultraviolet detection, characterized in that: The detector adopts a vertical heterojunction structure, wherein the first layer is a conductive substrate, including but not limited to molybdenum glass, ITO glass or FTO glass, preferably ITO glass, the second layer is an n-type semiconductor film, including but not limited to ZnO, TiO2 film, preferably TiO2 film, the third layer is a Bi2O3 intermediate layer, the fourth layer is a p-type semiconductor film, including but not limited to MoO3, WO3 and NiO film, preferably NiO film, and the fifth layer is a composite ultraviolet window electrode formed by the above protective layer and silver nanowires.
Citation Information
Patent Citations
Silver nanowire-biological material composite transparent conductive film and preparation method and application thereof
CN114038623A
Multiband composite photoelectric detector based on Bayer model and preparation method thereof
CN114927618A
Composition and organic insulator prepared using the same
US20080308793A1
Method for producing transparent conductive film, transparent conductive film, transparent conductive substrate and device comprising the same
US20110229737A1
Method of preparing thin film, thin film, apparatus for preparing thin film, and electronic device including thin film
US20130034708A1